Threshold effect on the femtosecond laser-induced periodic subwavelength structure: An analytical approach. (February 2023) - Wang, Bing; Wang, Yang; Song, Haiying; Cheong Lam, Yee; Memara Shaymaa, Elshaimaa; Liu, Shibing
Graphical abstract: Highlights: Surface phase-locking resonance dominates the self-formation of ripple structures. Analytical solution of threshold fluence for self-formation of ripple structures is provided. PIC simulation results are consistent well with the theoretical model. Coulomb ablation & direct ablation is experimentally verified. Abstract: For linearly polarized femtosecond laser-induced periodic nanostructures on a metal surface, the underlying physics of self-formation patterns is yet to be fully explained. We demonstrated here that the stabilized periodic interface electrostatic field (Coulomb field) arising from the surface phase-locking resonant dominates the self-formation of ripple structures. The kinetics of ultrafast laser ablation on solid surface were discussed. The threshold fluence and upper limit fluence for self-formation of ripple structures were calculated. The underlying mechanisms were clarified with both simulation and experimental results. Analytical formula for the interspace between ripples (i.e., wavelength of surface Langmuir wave) was developed. As illustrated by the experimental results, the competition of the two ablation mechanisms, namely surface Coulomb ablation and direct ultrafast laser ablations, was shown to result in distinct structuring patterns for a typical Gaussian pulse laser irradiation on the target surface at the appropriate laser energy fluence.